1991
DOI: 10.1111/j.1745-9125.1991.tb01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Bars, Blocks, and Crimes Revisited: Linking the Theory of Routine Activities to the Empiricism of “Hot Spots”*

Abstract: Anticipating recent developments in routine activities theory, Roncek and Bell (1981) found that bars and taverns had detrimental eflects on crime on residential city blocks in Cleveland for 1970. We replicate and extend their work by examining the effects of recreational liquor establishments (i.e., taverns and cocktail lounges) on crime from 1979 to 1981 on Cleveland's residential city blocks. The number of such businesses on residential city blocks has positive and statistically signifcant eflects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
364
1
7

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(389 citation statements)
references
References 26 publications
11
364
1
7
Order By: Relevance
“…Studies have consistently found a positive relationship between the proportion of racial/ ethnic minorities and the rate of crime in neighborhoods and cities (Krivo and Peterson 1996;McNulty 2001;Ouimet 2000;Roncek 1981;Roncek and Maier 1991). Scholars often conclude from this evidence that the presence of more racial/ethnic minorities leads to more crime, despite the fact that these studies almost always utilize cross-sectional data.…”
mentioning
confidence: 88%
“…Studies have consistently found a positive relationship between the proportion of racial/ ethnic minorities and the rate of crime in neighborhoods and cities (Krivo and Peterson 1996;McNulty 2001;Ouimet 2000;Roncek 1981;Roncek and Maier 1991). Scholars often conclude from this evidence that the presence of more racial/ethnic minorities leads to more crime, despite the fact that these studies almost always utilize cross-sectional data.…”
mentioning
confidence: 88%
“…These factors restrict social interaction among residents, which in turn impedes informal social control and order maintenance, and reduces the willingness to intervene on another's behalf. More recent work has also suggested that a greater number of single-parent households in the neighborhood reduce the ability to provide informal social control that would otherwise reduce delinquency (Roncek and Maier 1991;Rountree and Warner 1999). As the community's concern for the collective environment and its capacity to monitor and control behavior decreases, crime increases.…”
Section: The Effect Of Residential Instability On Crimementioning
confidence: 99%
“…Researchers have found that the presence of special-purpose structures, such as bars and taverns, high schools, convenience stores, rapid transit stations, or high-rise buildings may increase crime in their immediate vicinity (Roncek and Meier, 1991;Spelman, 1993;Block and Block, 1995;Block and Block, 1998).…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 99%